Escrevivências trans* como potência - Dias, Alfrancio Ferreira (2020)
In this text, I discuss a gender analysis stemmed from the movement of trans* Escrevivências.[1] In the first part of this work, I discuss how trans* writing is a boost for trans* self-knowledge, thus legitimizing new ways of producing knowledge about such subjects from themselves, stimulating me to describe them instead of theorizing about their lives. In the second part, I discuss the emergence of a trans* pedagogy that develops teaching, broadening the representativeness of this knowledge, based on a pedagogical approach based on the principles of teaching as trans* (feminist self-revelation that strengthens/widens spaces of trans* experiments), teaching about trans* (providing exposure to the trans* universe in teaching), and teaching with trans* epistemologies (to say that trans* teaching is not only embedded in other practices of knowledge production, it is, epistemological, itself, that is to say, producer of knowledge).